Benchmarking is a method for developing educational institutions - Alshiadi, Moza Ali Obied; Al-Ghanbosi, Salem Salim Mohammed; Al-Harithi, Aisha Salem Ali (Journal of Educational and Psychological Sciences, 2021)
The study aimed to highlight the theoretical and intellectual foundations of the importance of benchmarking as a new entry point for the development of educational institutions through taking advantage of competing partners in the educational field. The study used the documentary descriptive approach leading to a set of results, including: The diversity of benchmarking patterns provides an opportunity to benefit from them in educational institutions, and determining the requirements for the application of benchmarking in each institution based on its specific need which differs from one institution to another, in addition to many benefits that are greatly beneficial to educational institutions that apply benchmarking with quality and professionalism. The study provided a set of recommendations; Most notably: building partnerships based on development and improvement through the application of benchmarking as it is an effective tool to gain benefit from distinguished institutions locally and internationally. It is also possible to employ (classification and academic accreditation) obtained by educational institutions to reach the comparative partner easily and in accessible way.